Weight-for-Age Percentile as a Pediatric Predictor of Emergency Department Outcome. (September 2019) - Naik, Vishal; Lefaiver, Cheryl; Dervishi, Avni; Havalad, Vinod
This study is a retrospective cohort study that examines the association between weight-for-age percentile and pediatric admission incidence from the emergency department (ED) for all diagnoses. The charts of 1432 pediatric patients under 18 years with ED visits from 2013 to 2015 at a tertiary children's hospital were reviewed. Analyses of subject age/weight stratifications were performed, along with ED disposition, reason for visit, and Emergency Severity Index (ESI). Multivariable logistic regression models were used to evaluate the independent effect of weight-for-age percentile on ED disposition while controlling for age, ESI, and reason for visit. Underweight subjects were more likely to be admitted than their normal weight counterparts when analyzed overall (odds ratio [OR] = 2.58, P < .01) and by age: less than 2.0 years of age (OR = 2.04, P = .033), between 2.01 and 6.0 years of age (OR = 8.60, P = .004), and between 6.01 and 13.0 years of age (OR = 3.83, P = .053). Younger age (OR = 0.935, P < .001) and higher acuity (OR = 3.49, P < .001) were also significant predictors of admission. No significant associations were found between weight and likelihood of admission for patients older than 13.01 years or between overweight/obese weight categories and admission for any age subgroups. This study suggests that underweight children younger than 13 years are at higher risk to be admitted from the ED than their normal weight, overweight, and obese counterparts. Even when controlling for other key factors, such as the ESI, a lower weight-for-age percentile was a reliable predictor of hospitalization.